Associational Involvement in Dutch Municipalities and Neighbourhoods: Does Ethnic Diversity Influence Bonding and Bridging Involvement?. (29th June 2015) - Savelkoul, Michael; Gesthuizen, Maurice; Scheepers, Peer
Abstract : We test whether ethnic diversity in Dutch neighbourhoods and municipalities drives down associational involvement and build on earlier research in two important ways. First, we explicitly take into account the ethnic composition of local voluntary associations, distinguishing involvement in bonding (only in-group members) and bridging (with out-group members) associations. Second, we aim to explain relationships between ethnic diversity and associational involvement, testing two competing sets of predictions derived from conflict and contact theories. Using data from the Netherlands Longitudinal Lifecourse Study (2013), ethnic diversity turns out to hardly affect associational involvement negatively. Only for leisure associations, living in ethnically more diverse municipalities substantially decreases the likelihood to be involved in bonding associations, whereas higher levels of neighbourhood ethnic diversity increase the likelihood to be involved in bridging associations. Moreover, ethnic diversity indirectly affects associational involvement via interethnic contact. Higher levels of ethnic diversity increase interethnic contact which, in turn, is negatively related to involvement in bonding associations. Whereas higher levels of ethnic diversity in neighbourhoods increase perceptions of ethnic threat, these perceptions decrease with higher levels of ethnic diversity in the municipality. Perceptions of ethnic threat do not, however, affect associational involvement. Our results shed more light on the direct and indirect relationships between ethnic diversity and bonding and bridging associational involvement.